Comportamiento agronómico y valoración nutricional de la asociación flemingia (Flemingia macrophylla) mas clitoria (Clitoria ternatea) con pasto saboya (Panicum maximun) Y pasto brachiaria (Brachiaria decumbens) - Meza Vinces, Teodoro Manuel (2011)
In the property "María" of the Technical State University of the canton Quevedo, located in the km 7 of the Road Quevedo. The Connection, county of Ríos, county of Ríos was determined the agronomic "Behavior and nutritional value of the association of more Flemingia (Flemingia macrophylla) Clitoria (Clitoria ternatea) with grass Saboya (Panicum maximun) and grass Brachiaria (Brachiaria decumbens)" in different states of maturity, where they took as objectives to analyze the agronomic behavior of the gramineous-leguminous associations and to carry out the analyses bromatológicos to determine the nutritional value, using a design of complete blocks at random (DCA). In the simple effect of the grass, the association more Flemingia Clitoria with grass Saboya obtained the best indexes in the variables root (510,98 g) weight, forage (361,28 g) weight, weight of leaves (121 g), shaft (209,32 g) weight and relationship leaves hoja: tallo (0,69). And the best relationship leaves air he/she showed up in the association of more Flemingia Clitoria with grass Brachiaria with 1,78. In the simple effect of the ages the highest results in the variables forage weight, shaft weight and relationship leaves aérea: parte radicular they corresponded to the age of 140 days. The best index for the variable root weight was shown in the age of 110 days and the best root weight and relationship hoja: tallo was reported to the 80 days of age. In the interaction of the associations for the ages, the best indexes in root (686,7 g) weight, forage (429,45 g) weight, weight of leaves (156,9 g), shaft (256,9 g) weight and relationship hoja: tallo (1,01), they register to the 80 and 110 days in the association of more Flemingia Clitoria with the grass Saboya; and the best relationship hoja: tallo (1,01 g) and relationship leaves aérea:parte radicular (3,33) with the association of Flemingia with grass Brachiaria to the 80 days. The protein greater levels were obtained with the association of more Flemingia Clitoria with grass Saboya to the 80 and 110 days with the 10,97 and 12,39%. And the lowest fiber level is reported in the association of more Flemingia Clitoria with grass Brachiaria to the 80 days with 34,70%. For the composition microbiológica at 80 140, the tall populations in bacterias, actinomicetes, mushrooms, solubilizadores of P and fixers of N asimbiótico showed up with the association of more Flemingia Clitoria and grass Saboya. The bigger than colonization percentage and endófitos density to the 80 and 140 days showed up in the association of more Flemingia Clitoria and grass Brachiaria. However the biggest actinomicetes populations and celulolíticos showed up in the association of Flemingia with grass Brachiaria. For the obtained results you confirmed the outlined hypotheses: "The nutritious value of the gramineous-leguminous association more Flemingia Clitoria with grass Saboya for the three court ages will be superior" and "The gramineous-leguminous association more Flemingia (Flemingia Macrophylla) Clitoria (Clitoria ternatea) with grass Saboya (Panicum maximun) will show the biggest production of biomass in the different states of maturity."